Smart spring powered generator / Mohd Syahir Abdul Rahman ...[et al.] - Abdul Rahman, Mohd Syahir; Lop, Mohamad Annas; Abdul Samad, Mohamed Farid; Mohamad, Zulfakri; Alip, Rosalena Irma (UiTM Press, 2015)
Recently, 94.8% of Malaysia’s electricity has been generated from fossil fuels, which also the main polluters for the atmosphere in Malaysia. Efforts have been made to generate electricity via renewable energies, but the percentage is still low. To overcome this problem, this project proposes a low cost spring powered electric generator. The spring powered electric generator model will be constructed with multiple spring controlled by hydraulic system. The actual system will be embedded under the road since it needs the pressure of the vehicles to stretch the spring coil. Pressure exerted by the vehicle’s weight from the road users will be delivered in the spring by the hydraulic system and will be stored as spring force. When the spring is fully stretched it will alert the sensors and will move the motor. This process will generate electricity continuously for several hours depends on how many springs have been fully stretched by the weight of the vehicles. The generated electricity can be used to power up roadside facilities such as traffic lights, street lights and public toilets. This can help to cut down the electricity cost without any pollution to the atmosphere. For this system, NI myRIO-1900 will be used to control the hydraulic system and the monitoring system. As for conclusion, this project will present a model that can generate electricity through spring force to fulfill the demand of generating electricity through renewable energy at low cost. A prototype of a new renewable energy system that produce electricity at low cost have been designed. DC generator 2 with the gearing system has been selected for use in this Smart Spring Powered Generator system based on their best performance and increase the speed of the DC generator shaft that produce the highest electricity. The higher speed shaft of the DC generator rotate will increase the output power of this system. The output power of this project prototype system is 26mW. For now, the application that can used from this project prototype are turn ON the LED lamp.